Trust, emotion, resonance, and relevance: Norwegian teens reactions to anti-vaping campaigns - Bente Schøning; Sarah E. Rosenbaum; Torkjel M. Sandanger; Jo Røislien; Charlotte Wien (BMC Public Health, 2026)
Abstract Background Vaping among adolescents is an emerging public health concern, driven by increasing uptake and potential health risks. In Norway, e-cigarette use among young teenagers persists despite regulatory measures. Public service announcements (PSAs) are widely used to prevent vaping; however, evidence on how young adolescents perceive and engage with such messages remains limited. This study explores how Norwegian teenagers experience and evaluate anti-vaping PSAs, with particular attention to source of credibility, emotional resonance, and perceived effectiveness. Methods We conducted a qualitative study using semi-structured interviews with six adolescents aged 13–14 years from three schools in Tromsø, Norway. Participants were recruited through purposive convenience sampling. Each participant viewed four anti-vaping PSAs representing different communication strategies. Data were analyzed using reflexive thematic analysis, informed by the Perceived Effectiveness (PE) framework and the Think-before-you-talk (TENK) ethical framework to guide data interpretation of credibility, emotional engagement, and message reception. Results Participants identified peer messengers as more credible and relatable than adults or authority figures. PSAs that evoked emotional responses—such as fear, empathy, or discomfort—were perceived as more engaging and memorable than those emphasizing factual information alone. However, participants also expressed a need for clear, concrete explanations of vaping-related health risks. Emotional impact influenced both perceived effectiveness and willingness to share content, with social sharing framed as an important component of message diffusion among peers. Conclusions The findings suggest that anti-vaping PSAs targeting young adolescents may prioritize emotionally engaging content, incorporate peer-based messaging, and provide clear, accessible health information. Recognizing adolescents as both recipients and active disseminators of health messages may enhance the reach and impact of public health campaigns.